Jim Blinn's corner : notation, notation, notation - Blinn, Jim (Morgan Kaufmann series in computer graphics and geometric modeling., 2003)
The third entry in the Jim Blinn's Corner series, this is, like the others, a handy compilation of selected installments of his influential column. But here, for the first time, you get the "Director's Cut" of the articles: revised, expanded, and enhanced versions of the originals. What's changed? Improved mathematical notation, more diagrams, new solutions. What remains the same? All the things you've come to rely on: straight answers, irreverent style, and innovative thinking. This is Jim Blinn at his bestnow even better. Highlights Features 21 expanded and updated installments of "Jim Blinn's Corner," dating from 1995 to 2001, and never before published in book form. Includes "deleted scenes"tangential explorations that didn't make it into the original columns. Details how Blinn represented planets in his famous JPL flyby animations. Explores a wide variety of other topics, from the concrete to the theoretical: assembly language optimization for parallel processors, exotic usage of C++ template instantiation, algebraic geometry, a graphical notation for tensor contraction, and his hopes for a future world. *Features 21 expanded and updated installments of "Jim Blinn's Corner," dating from 1995 to 2001, and never before published in book form. *Includes "deleted scenes"tangential explorations that didn't make it into the original columns. *Details how Blinn represented planets in his famous JPL flyby animations. *Explores a wide variety of other topics, from the concrete to the theoretical: assembly language optimization for parallel processors, exotic usage of C++ template instantiation, algebraic geometry, a graphical notation for tensor contraction, and his hopes for a future world.